343 CISPLATIN-INDUCED DEATH OF ENDOTHELIAL CELLS. (1st January 2005) - Dursun, B.; He, Z.; Somerset, H.; Jani, A.; Faubel, S.; Edelstein, C. L.
Abstract : Acute renal failure (ARF) is a complicaton of cisplatin, a widely used chemotherapeutic agent. The role of vascular injury in cisplatin-induced ARF is not known. Caspases are a family of cysteine proteases that mediate cell death. Our aim was to determine the role of caspases in cisplatin-induced endothelial cell death. Cultured pancreatic microvascular endothelial (MS-1) cells were exposed to 10 μM and 50 μM doses of cisplatin for 24 hours. Cells were then treated with 50 μM of the pancaspase inhibitor, Q-VD-OPH. Caspase-3 activity was measured by the fluorescent substrate DEVD-AMC. ATP was measured using the bioluminescence assay. ATP levels (nmol/min/μg) were 171 ± 9 in control cells (C), 177 ± 10 in 10 μM cisplatin (P=NS vs C), 180 ± 12 in 10 μM cisplatin plus Q-VD-OPH (P=NS vs 10 μM cisplatin), 24 ± 5 in 50 μM cisplatin (P≤0.001 vs C, P≤0.001 vs 10 μM cisplatin) and 7 ± 1 in 50 μM cisplatin plus Q-VD-OPH (P=NS vs 50 μM cisplatin). Cell membrane damage as asssessed by LDH release (%) into the medium was 17 ± 1 in control cells (C), 37 ± 3 in 10 μM cisplatin (P≤0.001 vs C), 8 ± 1 in 10 μM cisplatin plus Q-VD-OPH (P≤0.001 vs 10 μM cisplatin), 57 ± 2 in 50 μM cisplatin (P≤0.001 vs C, P≤0.001 vs 10 μM cisplatin) and 13 ± 2 in 50 μM cisplatin plus Q-VD-OPH (P≤0.001 vs 50 μM cisplatin). Caspase-3 activity (nmol/min/mg) was 437 ±31 in control cells (C), 598 ± 26 in 10 μM cisplatin (P=NS vs C), 123 ± 7 in 10 μM cisplatin plus Q-VD-OPH (P≤0.001 vs 10 μM cisplatin), 2408 ± 489 in 50 μM cisplatin (P≤0.001 vs C, P≤0.001 vs 10 μM cisplatin) and 84 ± 4 in 50 μM cisplatin plus Q-VD-OPH (P≤0.001 vs 50 μM cisplatin). The cells were stained with the DNA-specific dyes Hoechst 33342 and propidium iodide (PI). Cells treated with 50 μM cisplatin displayed extensive PI staining indicative of loss of membrane integrity and necrosis. Lower concentrations (10 μM) of cisplatin excluded PI and showed nuclear staining mostly by Hoechst, with condensed, pyknotic and fragmented nuclei which is characteristic of apoptosis. In summary, these results in cisplatin-treated endothelial cells demonstrate: 1) a dose- dependent decrease in ATP levels; 2) a dose-dependent increase in cell membrane damage and caspase-3 activity; 3) lower doses induce mainly apoptosis while high doses induce necrosis; 4) a pancaspase inhibitor is protective against cell membrane injury. In conclusion, the role of endothelial cell injury in cisplatin-induced ARF merits further study.